Synthetic studies of ecteinascidin 743 and fennebricin B - Le, Vy Hoang, author; Williams, Robert M., advisor; Kennan, Alan J., committee member; Finke, Richard G., committee member; Luger, Karolin, committee member (Colorado State University. Libraries, 2017)
Ecteinascidin 743 (Et-743, trabectidin or Yondelis®) possesses an impressive antitumor activity that it was approved for treatments of several cancer types worldwide. Since this natural product only presents as a trace amount in the nature, the main supply of this drug for research and commercial use is from laboratory synthesis. Many syntheses of Et-743 have been reported including three total syntheses, two formal syntheses and two semisyntheses. The biological activities of fennebricin B were unknown due to the scarcity of this natural product. However, fennebricin B share a common pentacyclic core with Et-743, thus may also possess interesting biological activities. Our group completed our formal synthesis of the natural product in 2008, featuring the Pictet-Spengler reaction to construct the pentacyclic core of Et-743. Our work, however, also produced both desired and undesired pentacycle without selectivity. We herein described an improved formal synthesis of Et-743 employing bromine auxiliary to generate the pentacylic core of Et-743 with the desired regioisomer as the only product. This approach was also utilized in the synthetic studies toward the total synthesis of fennebricin B.